Secretome Profiling of Atlantic Salmon Head Kidney Leukocytes Highlights the Role of Phagocytes in the Immune Response to Soluble β-Glucan - Iliev, Dimitar B.; Strandskog, Guro; Sobhkhez, Mehrdad; Bruun, Jack A.; Jørgensen, Jorunn B. (Frontiers in Immunology, 2021)
β‐Glucans (BG) are glucose polymers which are produced in bacteria and fungi but not in vertebrate organisms. Being recognized by phagocytic leukocytes including macrophages and neutrophils through receptors such as dectin-1 and Complement receptor 3 (CR3), the BG are perceived by the innate immune system of vertebrates as foreign substances known as Pathogen Associated Molecular Patterns (PAMPs). The yeast-derived BG has been recognized for its potent biological activity and it is used as an immunomodulator in human and veterinary medicine. The goal of the current study was to characterize the immunostimulatory activity of soluble yeast BG in primary cultures of Atlantic salmon (Salmo salar) head kidney leukocytes (HKLs) in which phagocytic cell types including neutrophils and mononuclear phagocytes predominate. The effect of BG on the secretome of HKL cultures, including secretion of extracellular vesicles (EVs) and soluble proteins was characterized through western blotting and mass spectrometry. The results demonstrate that, along with upregulation of proinflammatory genes, BG induces secretion of ubiquitinated proteins (UbP), MHCII-containing EVs from professional antigen presenting cells as well as proteins derived from granules of polymorphonuclear granulocytes (PMN). Among the most abundant proteins identified in BG-induced EVs were beta-2 integrin subunits, including CD18 and CD11 homologs, which highlights the role of salmon granulocytes and mononuclear phagocytes in the response to soluble BG. Overall, the current work advances the knowledge about the immunostimulatory activity of yeast BG on the salmon immune system by shedding light on the effect of this PAMP on the secretome of salmon leukocytes.